Analisis Psikologis Tokoh Utama Dalam Novel “Aku Tak Membenci Hujan’’ Karya Sri Puji Hartini - Rismayanti Rismayanti; Tia Latifah (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2024)
This article aims to analyze the psychological aspects of the main character in the novel "Aku Tak MemHAT Hujan" by Sri Puji Hartini. Using a qualitative approach, this study examines the internal conflict faced by the main character and the influence of the environment on character development. The results of the analysis show that the main character experiences significant changes in her life perspective and interpersonal relationships, where traumatic experiences play an important role in the process of self-acceptance. This study also discusses how social interactions and emotional support from those closest to her help the main character in her psychological journey. Thus, this article aims to provide insight into the psychological complexity of the main character and its relevance in the context of everyday life.